An investigation on the dressing contact behavior between vitrified bonded CBN abrasive wheel and diamond grit dresser. (October 2020) - Li, Min; Ding, Wenfeng; Zhao, Zhengcai; Dai, Chenwei; Xu, Jiuhua
Highlights: Trajectory length is introduced to explain the wear behavior of diamond grit dresser and V-CBN abrasive wheel. AE RMS voltage can be applied to reflect a sudden wear increase of diamond grit. Strong contact will make vitrified bond compounds of abrasive wheels melt and adhere on diamond grit surface. Shorter dressing trajectory length of 0.212 μm will produce a better ground surface and a higher grinding ratio. Abstract: In order to better understand the dressing behavior, an investigation was carried out to detect the contact zone between vitrified bonded cubic boron nitride (V-CBN) abrasive wheel and diamond grit dresser. The grinding experiment of single diamond grit dresser on V-CBN abrasive segment was designed and conducted to approach the actual dressing process. The moving trajectory during dressing was calculated and discussed. Acoustic emission (AE) signals were applied to evaluate the wear progression of V-CBN abrasive wheel. Results obtained discovered that the different trajectory length would result in different wear patterns of diamond grit dresser and vitrified bond of V-CBN abrasive wheel. With the increase of wear ratio, the AE root-mean-square (RMS) voltages also had an increasing trend during dressing V-CBN wheel. Furthermore, a shorter dressing trajectory length produced a lower and more stable surface roughness, a lower tool radial wear and a higher grinding ratio in the grinding experiment of Inconel 718 nickel-based superalloy.